Utilization management in the clinical laboratory and other ancillary services - Lewandrowski, Kent; Sluss, Patrick M. (Cham, Switzerland : Springer, 2017)
This book is the first comprehensive text on utilization management in the clinical laboratory and other ancillary services. It provides a detailed overview on how to establish a successful utilization management program, focusing on such issues as leadership, governance, informatics, and application of utilization management tools. The volume also describes ways to establish utilization management programs for multiple specialties, including anatomic pathology and cytology, hematology, radiology, clinical chemistry, and genetic testing among other specialties. Numerous examples of specific utilization management initiatives are also described that can be imported to other heath care organizations. A chapter on utilization management in Canada is also included. Edited by an established national leader in utilization management, Utilization Management in the Clinical Laboratory and Other Ancillary Services is a valuable resource for physicians, pathologists, laboratory directors, hospital administrators, and medical insurance professionals looking to implement a utilization management program.
Healthcare Reform and its Impact on Medical Reimbursement -- Utilization management in the clinical laboratory: an introduction and overview -- Effective Governance Structure and Management of Utilization Programs -- Informatics, Analytics and Decision Support in Utilization Management -- Utilization Management Employing Test Interpretations and Algorithms -- Calculating Costs and Savings in Utilization Management -- Benchmarking and Management Metrics in Utilization Management -- Laboratory Formularies -- Utilization and Other Resource Management in Clinical Chemistry -- Utilization Management in the Routine Hematology Laboratory -- Patient Blood Management -- Utilization Management of Blood Derivatives -- Utilization Management in the Clinical Microbiology Laboratory -- Utilization Management in a Large Community Hospital -- Utilization Management: The Role of Reference Laboratories -- Utilization Management in Anatomic Pathology -- Utilization Analysis in Hematopathology -- Laboratory Utilization -- Test Utilization: Controlling costs in Reference Laboratory Testing -- Utilization Management of Genetic Testing -- The Use of Physician Profiling and Prior Approval (Gatekeeping) in Utilization Management in the Clinical Laboratory -- Test utilization: The Essential Role of the Clinical Consultant -- The Role of the Genetic Counselor in Utilization Management -- Utilization Management in Radiology -- Strategies for the Clinical and Financial Management of Drug Utilization -- Laboratory Utilization Management in Canada -- Utilization Management Initiatives That Can Be Imported into Health Care Systems.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on October 29, 2021).
WorldCat record variable field(s) change: 050
Keywords: Medical care -- Utilization review; Utilization Review; Ancillary Services, Hospital; Clinical Laboratory Services; Cost Control; Health Services -- statistics & numerical data; Marketing Research; Fulltext; Internet Resources